The Impact of Financial Shock Factor and Financial Well-being Factor on the Resilience of Malaysian B40 Household - Ariffin, Ariezan Zainal (Universitas Indonesia Membangun (Inaba), 2023)
The Coronavirus (Covid-19) pandemic that once affected a country in the past has left various impacts, including financial shocks such as job loss, increased healthcare expenses, and heightened financial stress among low-income B40 households in Malaysia. Financial well-being can serve as a turning point to address these financial shocks, with the presence of financial literacy and access to financial services enabling communities to overcome financial crises. In this study, the researcher will examine three main objectives: to assess the financial shock factors and financial well-being factors affecting the resilience of B40 households. Additionally, the researcher aims to explore the relationship between financial shocks and financial well-being and its impact on resilience. Finally, the researcher seeks to find solutions to the issues that arise. This study utilizes data from 102 respondents from the states of Sabah and Terengganu collected through survey questionnaires. Multiple regression analysis using the Statistical Package for the Social Sciences (SPSS) is employed to examine the financial shock and financial well-being factors. Pearson correlation analysis is also used to assess the relationship between these two variables. The study findings indicate that the Covid-19 pandemic is a financial shock factor among B40 households, and financial literacy and access to financial services are financial well-being factors. Both of these factors are interrelated and have an impact on resilience. Based on the results provided, it is hoped that the government will continue to strengthen financial well-being, such as enhancing financial literacy and financial access among B40 households.